Edukasi Kesantunan Berbahasa dalam Kampanye Pengurangan Sampah Plastik Bersama Komunitas Geng Plastik Ija (GPI) - Wahyu Ningsih; Syech Adiwijaya Latief; Abdul Wahid; Anin Asnidar; Ratnawati Ratnawati; Nur Khadijah Razak; Maria Ulviani; Rosdiana Rosdiana; Iskandar Iskandar; Nor Rulmaisura binti Mohamad; Ainun Qalby (FKIP, Universitas Palangka Raya, 2026)
This community service program is an international initiative aimed at increasing public awareness of the importance of language politeness in environmental campaigns, particularly in efforts to reduce plastic waste. The program was carried out through collaboration between Universitas Muhammadiyah Makassar, Politeknik Besut Terengganu Malaysia, and the Geng Plastik Ija Terengganu community. The activities were conducted at Bukit Keluang Beach using a participatory approach that actively involved community members in the planning, implementation, and evaluation stages of the program. The activities included training on polite communication, simulations of persuasive language use in environmental campaigns, and direct practice of plastic waste reduction campaigns for the surrounding community. Through these activities, participants gained a better understanding of the importance of using polite and effective language in delivering environmental messages to society. The results showed an improvement in participants’ communication skills in environmental advocacy, increased public awareness regarding plastic waste reduction, and greater community participation in maintaining environmental cleanliness. Furthermore, this international collaboration also strengthened cross-cultural communication competencies and institutional cooperation in implementing community service activities oriented toward environmental sustainability.